Advances in endometrial cancer protein biomarkers for use in the clinic. (2nd January 2018) - Martinez-Garcia, Elena; Lopez-Gil, Carlos; Campoy, Irene; Vallve, Julia; Coll, Eva; Cabrera, Silvia; Ramon Y Cajal, Santiago; Matias-Guiu, Xavier; Van Oostrum, Jan; Reventos, Jaume; Gil-Moreno, Antonio; Colas, Eva
ABSTRACT: Introduction : Endometrial cancer (EC) is the fourth most common cancer in women in developed countries. The identification of sensitive and specific biomarkers to improve early detection of EC is crucial for an appropriate management of this disease, in which 30% of patients are diagnosed only at advanced stages, which is associated with high levels of morbidity and mortality. Despite major efforts and investments made to identify EC biomarkers, no protein has yet reached the stage of clinical application. Areas covered : This review gathers the numerous candidate biomarkers for EC diagnosis proposed in proteomic studies published from 1978 to 2017. Additionally, we summarize limitations associated with the proteomic technologies and study designs employed in those articles. Finally, we address new perspectives in EC biomarker research, including the comprehensive knowledge of previously suggested candidate biomarkers in conjunction with novel mass spectrometry-based proteomic technologies with enhanced sensitivity and specificity not yet applied to EC studies and a directed clinical perspective in the study design. Expert commentary : These ingredients could be the recipe to accelerate the application of protein biomarkers in the clinic.